PENGARUH BRAND IMAGE DAN FASHION LIFESTYLE THRIFT SHOP TERHADAP KEPUASAN KONSUMEN - Faldi Cesarian Putra; Islamuddin Islamuddin (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
This study aims to determine “The Influence of Brand Image and Fashion Lifestyle in Thrift Shops on Consumer Satisfaction (A Case Study of Students at Dehasen University Bengkulu)”. This research is a quantitative study, which focuses on the measurement of data and statistical analysis. The population in this study consisted of students of Dehasen University Bengkulu. The sampling technique used was purposive sampling, resulting in a total of 78 respondents. Data were collected through questionnaires and analyzed using SPSS version 25.  The results of the study show that: (1) there is a positive influence of the Brand Image variable on Consumer Satisfaction. Based on the partial test, the t-value was 2.998 with a significance of 0.003 < 0.05; (2) there is a positive influence of the Fashion Lifestyle variable on Consumer Satisfaction. Based on the partial test, the t-value was 7.328 with a significance of 0.000 < 0.05; (3) the variables Brand Image and Fashion Lifestyle simultaneously have a positive influence on Consumer Satisfaction. This is evidenced by the F-test results, where the F-value was 57.196, greater than the F-table value of 3.09, with a significance of 0.000 < 0.05. Keywords: Brand Image, Fashion Lifestyle, Consumer Satisfaction